Ex vivo lung perfusion in lung transplantation - A. P. Fabrika; E. P. Tychina; A. M. Bayramkulov; E. A. Tarabrin (Трансплантология (Москва))
Introduction. The number of lung transplants performed worldwide is not enough because of a shortage of suitable (ideal) donors, missed chances to use lungs from donors who died of cardiac arrest, the lack of resources to perform this technically complex operation in poor, developing countries and due to a number of other reasons.) The world literature sources contain information about an increase in the number of lung transplantations by using organs from non-ideal (suboptimal and marginal) donors. This became possible thanks to the technology of ex vivo normothermic perfusion of donor lungs.Aim. To demonstrate the possibilities in the assessment, therapy and restoration of the function of non-ideal (suboptimal and marginal) donor lungs by using the technique of ex vivo lung perfusion.Material and methods. We reviewed scientific articles published in the period from 2003 to 2023 in the PubMed and Google Scholar databases for the key query "ex vivo lung perfusion".Conclusion. The ex vivo lung perfusion technique is a promising and effective procedure for lung evaluation, recondition and regeneration for) transplantation. A rapid development of technologies for this treatment modality makes it possible to increase the number of lungs suitable for transplantation, reduce the number of post-transplant complications and mortality rates on the waiting list, and improve the outcomes of lung transplantations.